Identification and Phenotypic Characterization of ZEBRA LEAF16 Encoding a β-Hydroxyacyl-ACP Dehydratase in Rice - Liu, Ziwen; Wang, Zhiyuan; Gu, Han; You, Jia; Hu, Manman; Zhang, Yujun; Zhu, Ze; Wang, Yihua; Liu, Shijia; Chen, Liangming; Liu, Xi; Tian, Yunlu; et al. (Frontiers in Plant Science, 2018)
The chloroplast is a self-independent organelle and contains its own transcription and translation systems. The establishment of genetic systems is vital for normal plant growth and development. We isolated a rice zebra leaf 16 (zl16) mutant derived from rice cultivar 9311. The zl16 mutant showed chlorotic abnormalities in the transverse sectors of the young leaves of seedlings. The use of transmission electron microscopy (TEM) demonstrated that dramatic defects occurred in variegated zl16 leaves during the early development of a chloroplast. Map-based cloning revealed that ZL16 encodes a β-hydroxyacyl-ACP dehydratase (HAD) involved in de novo fatty acid synthesis. Compared with the wild type, a missense mutation (Arg164Trp) in the zl16 mutant was identified, which significantly reduced enzymatic activity and altered the three-dimensional modeling structure of the putative protein. ZL16 was ubiquitously expressed in various plant organs, with a pronounced level in the young leaf. A subcellular localization experiment indicated that ZL16 was targeted in the chloroplast. Furthermore, we analyzed the expression of some nuclear genes involved in chloroplast development, and found they were altered in the zl16 mutant. RNA-Seq analysis indicated that some genes related to cell membrane constituents were downregulated in the mutant. An in vivo metabolic assay revealed that the total fatty acid content in the mutant was significantly decreased relative to the wild type. Our results indicate that HAD is essential for the development of chloroplasts by regulating the synthesis of fatty acids in rice.